EFFECT OF USING LIME AND FLY ASH AS A CEMENT SUBSTITUTE FOR SOIL STABILITY - Dias Dwi Hatmoko; Ismanti, Sito; Rifa’i, Ahmad (KURVATEK, 2024)
Subgrade is the lowest layer that receives the load on it if it does not have carrying capacity that is allowed then need for soil stabilization. Chemical soil stabilization is often done with the addition of cement but the use of cement material will cost quite high, it is necessary to alternate other materials for the substitution of cement to reduce the implementation costs incurred. Cement will be replaced as a stabilizing material in this research with additional materials like lime and fly ash. In this research, soil material was taken from the Sentul – Karawang Toll Road Project STA 24+300, with fly ash from PT PUSRI as the stabilization material, and lime material obtained from the market in Yogyakarta. The stabilization material will be used with a fixed lime percentage of 4.2% of the dry weight of the soil, and fly ash at 1.4%, 2.1%, 2.8%, 3.5%, and 4.2% of the dry weight of the soil. The soil samples were tested for physical and mechanical properties, including Standard Proctor and California Bearing Ratio (CBR). All test results were compared to select one variation, which was then designated as the Optimum Mix Design (OMD) sample. The test results of the soil sample + 4.2% lime + 2.1% fly ash yielded a CBR value of 15.52%, indicating an increase of 1078.02% from the initial 1.44%, and were formally designated as an OMD sample. The CBR value satisfies the subgrade requirements, namely >6%.